(untitled) (Research, Society and Development, 2021)
The aim of this paper was to investigate the academic satisfaction levels of the CAMEAM-UERN Administration course. The construction of a satisfaction survey is important for the development of quality education, along with the conception of the students who are part of the course and of the study institution, as they are essential for potentialing of growth and quality of education. This research is qualitative and quantitative, exploratory and descriptive in nature. To this end, was used a questionnaire with 35 (thirty five) questions about student satisfaction regarding various aspects related to academic life, where they assigned values on a scale of 1 (one) to 5 (five) to state between nothing and fully satisfied, respectively, and was applied to the universe of 103 (one hundred and three) students from the 4th (fourth) to the 10th (tenth) period of the CAMEAM-UERN Administration course. After data collection, charts and tables were used to demonstrate the results obtained through statistical analysis, outlined in six (6) dimensions, related to personal satisfaction, with the course, teachers, colleagues and the physical environment of the institution, obtaining a positive result towards students satisfaction about most of the aspects addressed, and a possible attention to improvements in the data collected with the neutral results. The analysis of this study may be useful to the institution for actions to be taken to potentialing of satisfaction level of the students of the CAMEAM-UERN Administration course.